Automatic Target Recognition with Laser Signs - Olgun, Nevzat; Türkoğlu, İbrahim (Sakarya University, 2018)
Together with the developing technology, there has been a rapid increase in the number of studies on automatic identification and classification of targets. Cameras, radars and sonar systems are traditionally used in target identification problems. In these methods, the identification and classification of the targets are made by means of people or computer systems by taking their distinctive features into account. In this study, it is recommended to define and classify targets pointed with laser by using a single laser light source and detecting system, as opposed to conventional methods. The results obtained from the experimental studies made with the proposed system show that the approach of target detection by laser light points gives successful results.

Gelişen teknoloji ile birlikte hedeflerin otomatik olarak tanımlanması ve sınıflandırılması üzerine yapılan çalışmaların sayısında da hızlı bir artış yaşanmıştır. Hedef tanımlama problemlerinde geleneksel olarak kameralar, radarlar ve sonar sistemleri kullanılmaktadır. Bu yöntemlerde nesnelerin ayırt edici özellikleri dikkate alınarak tanımlama ve sınıflandırma işlemleri insanlar veya bilgisayar sistemleri aracılığı ile yapılmaktadır.  Bu çalışmada geleneksel yöntemlerin aksine tek bir lazer ışık kaynağı ve algılayıcı sistem kullanılarak lazer ile işaretlenen hedeflerin tanımlanması ve sınıflandırılması önerilmektedir. Önerilen sistem ile yapılan deneysel çalışmalarda elde edilen sonuçlar, lazer işaretleri ile hedef tespiti yaklaşımının başarılı sonuçlar verdiğini göstermektedir.
Lazer İşaretleri İle Otomatik Hedef Tanıma
Keywords: Computer Software; Bilgisayar Yazılımı